A Stunting Prevention Risk Factors Pathway Model for Indonesian Districts/Cities with a Stunting Prevalence of ≥30% - Fentiana, Nina; Achadi, Endang L; Besral, Besral; Kamiza, Abram; Sudiarti, Trini (Kesmas, 2022)
The prevalence of stunting in Indonesian children aged 0-23 months is a public health problem caused by direct and indirect factors. This study aimed to discover the path of the relationship between various risk factors and the stunting prevalence of ≥30% in 165 districts/cities in Indonesia. Data were obtained from the 2018 National Basic Health Research, National Socioeconomic Survey, and the Statistics Indonesia with a cross-sectional approach. The secondary data on stunting and risk factors were aggregated at the district/city level from individual data; children aged 0-23 months. The path analysis used to determine a stunting prevention model showed that antenatal care at the district/city level decreased stunting rates by at least 2.56% (b = -0.16; p-value = 0.04). A contraceptive user at the district/city level decreased stunting rates by 2.25% (b = -0.15; p-value = 0.05), and handwashing with soap at the district/city level by5.76%, (b = -0.24; p-value = 0.003). Antenatal care, contraceptive use, and handwashing with soap contributed to the reduction of stunting prevalence by18.18%. The study results suggested that districts/cities can play an important role in reducing stunting.